(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study was motivated by learning obstacles experienced by fifth-grade elementary students in understanding data representation using bar charts, particularly in determining scales and interpreting data. The study aimed to identify these obstacles and develop a didactical design based on Realistic Mathematics Education (RME) to reduce them. The research employed Didactical Design Research (DDR), consisting of prospective analysis, implementation, and retrospective analysis. Data were collected through diagnostic tests, observations, interviews, and analysis of students’ work. The findings indicate that the learning obstacles were epistemological and didactical in nature. The implementation of the RME-based didactical design improved student engagement and conceptual understanding of data representation, although learning outcomes varied due to differences in prior knowledge. This study recommends further research to apply similar didactical designs to other statistical topics and educational levels to enhance students’ numeracy literacy